UPAYA KONSULAT MALAYSIA DI PEKANBARU DALAM MEMELIHARA HUBUNGAN DIPLOMATIK MALAYSIA DI PROVINSI RIAU - Meichen Monalia Silaban; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Consulate of Malaysia Pekanbaru is the representative of Malaysian which aims to maintain diplomatic relations between Malaysia and Indonesia in Riau. Geographical location and similar cultural backgrounds are strategic values for Malaysia to achieve national interests and to increase efforts diplomatic relations. This study aims to explain how the efforts Consulate of Malaysia Pekanbaru to maintain Malaysia's diplomatic relations with Riau. This research uses neorealist perspective which is the state determines the best way to achieve national interests and level of nation-state analysis. The theory applied in this research is the theory of public diplomacy using the concept national interests and using qualitative research methods. The result of the research is the effort Consulate of Malaysia Pekanbaru to maintain diplomatic relations with Riau by using public diplomacy. Consulate of Malaysia Pekanbaru carries out public diplomacy towards the government and non-government to increase knowledge, to introduce Malaysia in Riau, to increase appreciation and public interest, and also influence society through the city development, economy, culture, tourism, health and education by introducing the qualifications of Malaysia. Keywords: Public Diplomacy, national interest, representative